Analysis of the subcellular localization of the Chlamydia trachomatis effector CteG and of its homologs in other Chlamydia species - Leal, Inês Pacheco (2022)
Chlamydiae are a large group of phylogenetically related obligate intracellular Gram-negative bacteria, that only grow within eukaryotic host cells. Among Chlamydiae, Chlamydia trachomatis is an exclusive human pathogen, causing ocular and genital infections. As all Chlamydiae, C. trachomatis manipulates human cells through a type III secretion system that enables the delivery into host cells of effector proteins that, in general, promote chlamydial growth and survival. In this work, the C. trachomatis effector associated with the Golgi (CteG) and its homologs in other Chlamydia species were studied. C. trachomatis CteG initially localizes at the Golgi complex, from ~20 h post-infection, and then starts localizing at the host plasma membrane (PM), from ~30 h post-infection. First, we aimed to test if twelve CteG homologs that are type III secreted by Yersinia can be transported by C. trachomatis into the cytoplasm of infected cells (i.e., translocated). For this, several C. trachomatis strains were generated. Immunofluorescence microscopy revealed that seven (out of twelve) CteG homologs were translocated into host cells. Furthermore, analysis of their subcellular localization indicated that some localized at the Golgi and PM, while others only at the Golgi or PM. Based on this, and considering the predicted secondary structure of CteG, we deduced regions in CteG that may determine its subcellular localization. To analyze this, several transfection plasmids and C. trachomatis strains were generated, enabling the expression of defined CteG truncated proteins. In transfected cells, immunofluorescence microscopy revealed that the C-terminal region of CteG was implicated in its localization at the plasma membrane. In infected cells, the immunofluorescence microscopy analysis was hampered by the low expression of CteG truncated proteins. Overall, this work enabled to define a group of Chlamydia CteG homolog effectors and to set the basis for additional analysis of the determinants of the subcellular localization of CteG.